Template-Mediated Biomineralization for Bone Tissue Engineering - Leiendecker, Alexander; Witzleben, Steffen; Schulze, Margit; Tobiasch, Edda (Current Stem Cell Research & Therapy, 2017)
Template-mediated mineralization describes a research field of materials chemistry that deals with templates influencing product formation of foremost inorganic functional materials and composites. These templates are usually organic compounds - as far as molecules with natural origin are involved, the terminology
Keywords: Biomineralization